Answer:
Jenna is correct.
Step-by-step explanation:
See attached image.
your answer is D hope this helps and mark for brainlest
Answer:
x=-1-5√17/2
Step-by-step explanation:
logo((x-2)(x+2))=2
logo(x²+3x-2x-6)=2
x²+3x-2x-6=10²
x²+x-6=100
x²+x-106=0
x=-1+5√17/2
514 divided by 28 equals 18.3571429
If you would like to solve the equation 3 * (3 * x - 1) + 2 * (3 - x) = 0, you can calculate this using the following steps:
3 * (3 * x - 1) + 2 * (3 - x) = 0
3 * 3 * x - 3 * 1 + 2 * 3 - 2 * x = 0
9 * x - 3 + 6 - 2 * x = 0
7 * x + 3 = 0
7 * x = - 3 /7
x = - 3/7
The correct result would be - 3/7.